Stroke health management: Novel strategies for the prevention of recurrent ischemic stroke - Jiang, Lili; Zhou, Yu; Zhang, Li; Wu, Lingling; Shi, Haibin; He, Bin; Wang, Yao; Liu, Qianghui; Ji, Xueli; Zhang, Xintong; Jiang, Lei; Sun, Hao (Frontiers in Neurology, 2022)
Objectives: To assess the effect of stroke health management model guided by stroke health managers based on patients' needs on the prognosis and recurrence of mild to moderate ischemic stroke patients. In addition, up-to-date evidence for healthcare resource allocation, planning and optimization is provided. Methods: This was a retrospective, observational, single center, history-controlled study with two groups according to the induction of the stroke health manager. For the control group, patients received standard medical care during hospitalization. The standard medical care consisted of advice on healthy lifestyle choices carried out by bed nurse, but no structured education, WeChat group or clinical consultation was provided. For the intervention group, in addition to standard medical care, patients received stroke health manager focus on health management and health education. After discharge the patients were followed up over telephone by the health manager to see if there was any recurrence or readmission. Results: From January 1, 2018 to December 31, 2020, 382 patients with acute ischemic stroke were enrolled in this study. In the univariate regression analysis, the SHM intervention was associated with a significant lower risk of recurrence (HR=0.459). We constructed a nomogram based on the filtered variables and also analyzed the association between the control group and the SHM intervention group among all subgroups using Cox proportional hazards models to assess the effect of stroke health management model. Most patients in this study had a total risk point between 170 and 270. The C-index value was 0.76, and the time-dependent AUC for predicting recurrence was >0.7. Conclusion: The stroke health manager-guided management model based on patient’s needs can better control stroke risk factors, significantly reduced the recurrence rate of mild to moderate ischemic stroke within one year.